(untitled) - Gause, Val (Lincolnwood, Illnois, USA, 1997)
With this practical guide, Val Gause offers an introduction to writing for school and community media. The book covers the practical techniques of print and electronic journalism, and discusses the roles of media ethics and professionalism.
Keywords: Mass media; Authorship,Juvenile literature